Computers and society modern perspectives - Baecker, Ronald M. (Oxford, United Kingdom Oxford University Press, 2019)
The last century has seen enormous leaps in the development of digital technologies, and most aspects of modern life have changed significantly with their widespread availability and use. Technology at various scales - supercomputers, corporate networks, desktop and laptop computers, the internet, tablets, mobile phones, and processors that are hidden in everyday devices and are so small you can barely see them with the naked eye - all pervade our world in a major way.

Computers and Society: Modern Perspectives is a wide-ranging and comprehensive textbook that critically assesses the global technical achievements in digital technologies and how are they are applied in media; education and learning; medicine and health; free speech, democracy, and government; and war and peace.

Ronald M. Baecker reviews critical ethical issues raised by computers, such as digital inclusion, security, safety, privacy,automation, and work, and discusses social, political, and ethical controversies and choices now faced by society. Particular attention is paid to new and exciting developments in artificial intelligence and machine learning, and the issues that have arisen from our complex relationship with AI.
1. Digital inclusion -- 2. Digital media and intellectual property -- 3. Computers in education and learning -- 4. Computers in medicine and health care -- 5. Free speech, politics, and government -- 6. Law and order, war and peace -- 7. Security -- 8. Safety -- 9. Privacy -- 10. Automation, work, and jobs -- 11. Artificial intelligence, explanations, trust, responsibility, and justice -- 12. Lifestyle -- 13. Epilogue -- 14. Afterword: Developments in autumn 2018.
Includes bibliographical references (pages [391]-516) and index.
Keywords: Computers and civilization; Artificial intelligence -- Social aspects; Computers -- Social aspects; Information technology -- Social aspects